Unveiling the power of diet and lifestyle in managing Crohn's disease - Artur Bialic; Kinga Bialic; Rafał Bakalarczyk; Paweł Majewski; Lucjan Bednarz; Karolina Szala-Czerwonka; Natalia Woś; Adrian Rejmer; Katarzyna Rojek; Karolina Wijas (Kazimierz Wielki University, 2023)
Introduction: Crohn's disease (CD) is an inflammatory bowel disease that can affect any part of the digestive tract. Onset, progression, complications and treatment are influenced by many genetic, environmental and dietary factors. Dietary management is very useful in a variety of gastrointestinal diseases, including CD. Some nutrients have been studied in animal models to exacerbate the disease, while others have strong scientific evidence from large studies in human populations, allowing conclusions to be drawn about their impact on the disease. Dietary management is now a well-established and important part of treatment, in addition to the use of systemic corticosteroids, aminosalicylates, immunomodulators (e.g. azathioprine, 6-mercaptopurine, cyclosporine, tacrolimus) or biologic therapies. State of knowledge: To test the associations between the intake of specific macronutrients and the course of CD, we searched the PubMed database focusing on articles about the effects of consumed food components and stimulants on the onset and progression of CD. Conclusion: Nutritional treatment plays an important role in the management of CD. An appropriate diet can make a significant contribution to reducing inflammation and attenuating the course and exacerbations of the disease. The intake of proteins, fats, carbohydrates, fiber and certain food additives has been shown in studies to influence the onset and course of CD.